Adenine Cu-MOF-based hydrogel composite material and preparation method and application thereof

By using adenine Cu-MOF-based hydrogel composite in wound healing materials, the problem of insufficient biocompatibility and healing effect in the prior art was solved, and significant pro-keratinocyte proliferation and wound healing effects were achieved.

CN119015487BActive Publication Date: 2025-02-25AIR FORCE MEDICAL CENT PLA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411141906.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-25
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of biocompatibility and healing effects during wound healing, especially in promoting keratinocyte proliferation and reducing scar production.

Method used

Adenine Cu-MOF-based hydrogel composite material is used, which is loaded on methacrylate gelatin hydrogel by copper metal organic framework [Cu2(Ad)2(SA)]•3DMA, and is crossed by solvent heat and light. The combination reaction is formed to ensure the biocompatibility and stability of the material.

Benefits of technology

This material significantly promotes keratinocyte proliferation at appropriate concentrations, has significant wound healing ability, and is biocompatible and stable, reducing scar production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119015487B_ABST
    Figure CN119015487B_ABST
Patent Text Reader

Abstract

The present invention provides an adenine Cu-MOF-based hydrogel composite material and a preparation method and application thereof, and relates to the technical field of MOF materials. The adenine Cu-MOF-based hydrogel composite material is composed of a copper metal organic framework loaded on a hydrogel; wherein the copper metal organic framework is [Cu2(Ad)2(SA)]·3DMA; wherein the hydrogel is methacrylated gelatin; wherein the mass ratio of the copper metal organic framework to the hydrogel is (0.1-1):(5-15). The adenine Cu-MOF-based hydrogel composite material of the present invention has good biocompatibility and stability, and the MOF has an obvious effect of promoting keratinocyte proliferation at an appropriate concentration, and has the potential to promote wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of MOF materials, and in particular to an adenine Cu-MOF-based hydrogel composite material and a preparation method and application thereof. Background Art

[0002] Promoting keratinocyte proliferation is of great significance in the process of skin wound healing. It can accelerate wound closure, help quickly cover the wound surface, and reduce the risk of infection. At the same time, in the re-epithelialization stage of wound healing, the proliferation and migration of keratinocytes are essential for the formation of a new epidermis. It can also reduce the formation of scars. Although some new materials have shown great potential in wound healing, issues such as biocompatibility and healing effects still need to be resolved before clinical application.

[0003] Metal-Organic Framework (MOF) materials, as a multifunctional material, also show potential in chronic wound healing because they have low toxicity and high biocompatibility, and can promote wound repair through their versatility and structural designability. MOF materials and hydrogel composites have also become one of the ideal materials for making wound dressings due to their good moisture retention, biocompatibility and biodegradability. They can keep the wound surface moist, provide a suitable microenvironment, and promote wound healing.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide an adenine Cu-MOF-based hydrogel composite material and a preparation method and application thereof. The adenine Cu-MOF-based hydrogel composite material has good biocompatibility and stability, and the adenine Cu-MOF-based hydrogel composite material of the present invention has a significant effect on promoting keratinocyte proliferation at an appropriate concentration and has a significant ability to promote wound healing.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] In a first aspect, the present invention provides an adenine Cu-MOF-based hydrogel composite material, wherein the adenine Cu-MOF-based hydrogel composite material is composed of a copper metal organic framework loaded on a hydrogel;

[0008] Wherein, the copper metal organic framework is [Cu2(Ad)2(SA)]•3DMA;

[0009] Wherein, the hydrogel is methacrylated gelatin;

[0010] Wherein, the mass ratio of the copper metal organic framework to the hydrogel is (0.1~1):(5~15).

[0011] Furthermore, the raw materials for preparing the Cu-MOF-based hydrogel composite material include the following components by mass percentage:

[0012] Copper metal organic framework 0.1~1%, hydrogel 5~15%, photocrosslinker 0.05~0.5%, and the balance is reaction solvent.

[0013] Furthermore, the photocrosslinking agent is lithium phenyl (2,4,6-trimethylbenzoyl) phosphinate.

[0014] Furthermore, the reaction solvent is water.

[0015] In a second aspect, the present invention provides a method for preparing the adenine Cu-MOF-based hydrogel composite material as described in the first aspect, the preparation method comprising the following steps:

[0016] The copper metal organic framework and the hydrogel are sequentially subjected to solvent thermal reaction and photo-crosslinking reaction, so that the copper metal organic framework is loaded on the hydrogel to obtain the adenine Cu-MOF-based hydrogel composite material.

[0017] Furthermore, the preparation method of the adenine Cu-MOF-based hydrogel composite material specifically comprises the following steps:

[0018] The copper metal organic framework, the hydrogel, the photocrosslinking agent and the reaction solvent are mixed to perform a solvothermal reaction to obtain a precursor of the hydrogel composite material;

[0019] The precursor of the hydrogel composite material is subjected to a photo-crosslinking reaction under the condition of blue light to obtain the adenine Cu-MOF-based hydrogel composite material.

[0020] Furthermore, the temperature of the solvent thermal reaction is 45-55°C.

[0021] Furthermore, the solvent thermal reaction time is 10 to 20 min.

[0022] Furthermore, the wavelength of the blue light is 400-450 nm.

[0023] Further, the temperature of the cross-linking reaction is 40-55°C;

[0024] Furthermore, the cross-linking reaction time is 10 to 20 s.

[0025] In a third aspect, the present invention provides a use of the adenine Cu-MOF-based hydrogel composite material as described in the first aspect in preparing a material for promoting skin wound healing and / or preparing a material for promoting keratinocyte proliferation.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention selects [Cu2(Ad)2(SA)]•3DMA as the copper metal organic framework, which has a better effect on promoting keratinocyte proliferation and higher stability than the current classic Cu-MOF, HKUST-1 and other metal organic framework materials, and has the potential to promote wound healing.

[0028] (2) The adenine Cu-MOF-based hydrogel composite material described in the present invention is formed by solvent thermal and photocrosslinking of [Cu2(Ad)2(SA)]•3DMA and methacrylated gelatin. The adenine Cu-MOF-based hydrogel composite material has good biocompatibility and stability. In addition, the adenine Cu-MOF-based hydrogel composite material of the present invention has a significant effect on promoting keratinocyte proliferation at an appropriate concentration and has a significant ability to promote wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 The graph shows the cell viability experimental results of Cu-AD-SA and HKUST-1.

[0031] Figure 2 X-ray powder diffraction patterns of Cu-AD-SA and Cu-AD-SA@GelMa under different conditions.

[0032] Figure 3 This is a cell cloning experiment result diagram provided for Test Example 4.

[0033] Figure 4A The results of the cell viability experiment under 3D co-culture of Cu-AD-SA@GelMa hydrogel composite materials with different concentrations.

[0034] Figure 4B This is the result of the cell viability experiment under 3D co-culture of HKUST-1@GelMa, Cu-AD-SA@HAMA, bM, and PCbM hydrogel composites.

[0035] Figure 5 This is the result of the cell live-dead staining experiment under MOF and hydrogel 3D co-culture. DETAILED DESCRIPTION

[0036] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0037] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In a first aspect, the present invention provides an adenine Cu-MOF-based hydrogel composite material, wherein the adenine Cu-MOF-based hydrogel composite material is composed of a copper metal organic framework loaded on a hydrogel;

[0040] Wherein, the copper metal organic framework is [Cu2(Ad)2(SA)]•3DMA;

[0041] Wherein, the hydrogel is methacrylated gelatin;

[0042] Wherein, the mass ratio of the copper metal organic framework to the hydrogel is (0.1~1):(5~15).

[0043] Among them, [Cu2(Ad)2(SA)]•3DMA is a Cu metal-organic framework material based on mixed ligands of adenine and succinic acid, hereinafter abbreviated as Cu-AD-SA. Among them, the hydrogel is methacrylated gelatin, hereinafter abbreviated as GelMa. The biocompatibility of the raw materials is good.

[0044] Furthermore, in [Cu2(Ad)2(SA)]•3DMA, Ad represents the organic ligand adenine, SA represents the auxiliary ligand succinic acid, and DMA represents dimethylacetamide. Compared with other metal organic framework materials, such as the current classic Cu-MOF, HKUST-1 and other metal organic framework materials, the copper metal organic framework Cu-AD-SA has a more significant effect on promoting keratinocyte proliferation and has higher stability, so it can further improve the ability to promote wound healing.

[0045] In the present invention, the adenine Cu-MOF-based hydrogel composite material is formed by solvent thermal and photocrosslinking of [Cu2(Ad)2(SA)]•3DMA and methacrylated gelatin, and has good biocompatibility and stability. In addition, the adenine Cu-MOF-based hydrogel composite material of the present invention has a significant effect on promoting keratinocyte proliferation at an appropriate concentration and has a significant ability to promote wound healing.

[0046] In an optional embodiment, the [Cu2(Ad)2(SA)]•3DMA is prepared by the following steps: organic ligand adenine, succinic acid, copper nitrate, N,N -Dimethylacetamide and water are mixed and subjected to a solvothermal reaction to obtain the [Cu2(Ad)2(SA)]•3DMA.

[0047] In an optional embodiment, the molar ratio of adenine, succinic acid and copper nitrate is 1:1:(2-4), for example, it can be 1:1:2, 1:1:2.5, 1:1:3, 1:1:3.5, 1:1:4, etc.

[0048] In an optional embodiment, each 0.04 mmol of copper nitrate corresponds to 1 to 4 mL (e.g., 1 mL, 1.5 mL, 2 mL, 2.5 mL, 3 mL, 3.5 mL, 4 mL, etc.) of N,N -dimethylacetamide and 0.5~2 mL (e.g., 0.5 mL, 0.8 mL, 1 mL, 1.2 mL, 1.5 mL, 1.8 mL, 2 mL, etc.) of water.

[0049] In an optional embodiment, during the preparation of the [Cu2(Ad)2(SA)]•3DMA, the temperature of the solvothermal reaction is 75-85°C, for example, 75°C, 76°C, 78°C, 80°C, 82°C, 85°C, etc.

[0050] In an optional embodiment, during the preparation of the [Cu2(Ad)2(SA)]•3DMA, the solvent thermal reaction time is 32 to 40 h, for example, 32 h, 34 h, 36 h, 38 h, 40 h, etc.

[0051] In an optional embodiment, in the adenine Cu-MOF-based hydrogel composite material, the mass ratio of the copper metal organic framework to the hydrogel is (0.1~1):(5~15);

[0052] Herein, “0.1-1” may be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc. Herein, “5-15” may be, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, etc.

[0053] In an optional embodiment, the raw materials for preparing the Cu-MOF-based hydrogel composite material include the following components by mass percentage:

[0054] Copper metal organic framework 0.1~1%, hydrogel 5~15%, photocrosslinker 0.05~0.5%, and the balance is reaction solvent.

[0055] Taking the total mass of the raw materials for preparing the Cu-MOF-based hydrogel composite material as 100%, the content of the copper metal organic framework (Cu-AD-SA) is 0.1-1%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., preferably 0.4-0.6%, and more preferably 0.5%.

[0056] Taking the total mass of the raw materials for preparing the Cu-MOF-based hydrogel composite material as 100%, the content of hydrogel (GelMa) is 5-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., preferably 8-12%, and more preferably 10%.

[0057] Based on the total mass of the raw materials for preparing the Cu-MOF-based hydrogel composite material as 100%, the content of the photocrosslinker is 0.05-0.5%, for example, it can be 0.05%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, etc., preferably 0.1-0.3%, and more preferably 0.2%.

[0058] In an optional embodiment, in the raw materials for preparing the Cu-MOF-based hydrogel composite material, the photocrosslinking agent is lithium phenyl (2,4,6-trimethylbenzoyl) phosphinate (LAP).

[0059] In an optional embodiment, in the raw materials for preparing the Cu-MOF-based hydrogel composite material, the reaction solvent is water.

[0060] In a second aspect, the present invention provides a method for preparing the adenine Cu-MOF-based hydrogel composite material as described in the first aspect, the preparation method comprising the following steps:

[0061] The copper metal organic framework and the hydrogel are sequentially subjected to solvent thermal reaction and photo-crosslinking reaction, so that the copper metal organic framework is loaded on the hydrogel to obtain the adenine Cu-MOF-based hydrogel composite material.

[0062] In an optional embodiment, the preparation method of the adenine Cu-MOF-based hydrogel composite material specifically comprises the following steps:

[0063] (a) mixing the copper metal organic framework, the hydrogel, the photocrosslinking agent and the reaction solvent, and performing a solvothermal reaction to obtain a precursor of the hydrogel composite material;

[0064] (b) subjecting the precursor of the hydrogel composite material to a photo-crosslinking reaction under blue light conditions to obtain the adenine Cu-MOF-based hydrogel composite material.

[0065] In an optional embodiment, in step (a), the temperature of the solvothermal reaction is 45-55°C, for example, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, etc.

[0066] In an optional embodiment, in step (a), the time of the solvothermal reaction is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, etc.

[0067] In an optional embodiment, in step (b), the wavelength of the blue light is 400-450 nm, for example, 400 nm, 402 nm, 405 nm, 408 nm, 410 nm, 415 nm, 420 nm, 425 nm, 430 nm, 435 nm, 440 nm, 445 nm, 450 nm, etc.

[0068] In an optional embodiment, in step (b), the temperature of the cross-linking reaction is 40-55°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 55°C, etc.

[0069] In an optional embodiment, in step (b), the cross-linking reaction time is 10 to 20 s, for example, it can be 10 s, 11 s, 12 s, 13 s, 11 s, 14 s, 15 s, 16 s, 17 s, 18 s, 19 s, 20 s, etc.

[0070] In a third aspect, the present invention provides a use of the adenine Cu-MOF-based hydrogel composite material as described in the first aspect in preparing a material for promoting skin wound healing and / or preparing a material for promoting keratinocyte proliferation.

[0071] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0072] Preparation Example 1

[0073] This preparation example provides a copper metal organic framework Cu-AD-SA, and the copper metal organic framework Cu-AD-SA is specifically prepared by the following steps:

[0074] 40 mg of organic ligand adenine, 40 mg of succinic acid and 80 mg of copper nitrate were mixed in 10.00 mL of N,N -dimethylacetamide and 5 mL of deionized water were mixed evenly and sealed in a vial; and then subjected to a thermal reaction at 80° C. for 48 h to obtain the copper metal organic framework Cu-AD-SA.

[0075] Example 1

[0076] This embodiment provides an adenine Cu-MOF-based hydrogel composite material, and the adenine Cu-MOF-based hydrogel composite material is specifically prepared by the following steps:

[0077] (1) First, freeze-dried GelMa was dissolved in deionized water containing LAP at 45°C in the dark to obtain a GelMa solution; then, Cu-AD-SA obtained in Preparation Example 1 was dispersed in the GelMa solution to obtain a mixed solution; finally, the mixed solution was stirred at 45°C in the dark for 15 min to obtain a uniform precursor of a hydrogel composite material;

[0078] The mixed solution includes, by mass percentage, 0.5% Cu-AD-SA, 10% GelMa, 0.2% LAP, and the remainder is water.

[0079] (2) The precursor of the hydrogel composite material obtained in step (1) is irradiated with blue light of 405 nm wavelength, and the cross-linking time is 15 s to obtain the adenine Cu-MOF-based hydrogel composite material.

[0080] Example 2

[0081] This embodiment provides an adenine Cu-MOF-based hydrogel composite material, and the adenine Cu-MOF-based hydrogel composite material is specifically prepared by the following steps:

[0082] (1) First, freeze-dried GelMa was dissolved in deionized water containing LAP at 45°C in the dark to obtain a GelMa solution; then, Cu-AD-SA obtained in Preparation Example 1 was dispersed in the GelMa solution to obtain a mixed solution; finally, the mixed solution was stirred at 55°C in the dark for 10 min to obtain a uniform precursor of a hydrogel composite material;

[0083] The mixed solution includes, by mass percentage, 0.5% Cu-AD-SA, 10% GelMa, 0.2% LAP, and the remainder is water.

[0084] (2) Using blue light with a wavelength of 400 nm to irradiate the precursor of the hydrogel composite material obtained in step (1), the cross-linking time is 20 s, and the adenine Cu-MOF-based hydrogel composite material is obtained.

[0085] Example 3

[0086] This embodiment provides an adenine Cu-MOF-based hydrogel composite material, and the adenine Cu-MOF-based hydrogel composite material is specifically prepared by the following steps:

[0087] (1) First, freeze-dried GelMa was dissolved in deionized water containing LAP at 45°C in the dark to obtain a GelMa solution; then, Cu-AD-SA obtained in Preparation Example 1 was dispersed in the GelMa solution to obtain a mixed solution; finally, the mixed solution was stirred at 50°C in the dark for 12 min to obtain a uniform precursor of a hydrogel composite material;

[0088] The mixed solution includes, by mass percentage, 0.5% Cu-AD-SA, 10% GelMa, 0.2% LAP, and the remainder is water.

[0089] (2) The precursor of the hydrogel composite material obtained in step (1) is irradiated with blue light of 410 nm wavelength, and the cross-linking time is 10 s to obtain the adenine Cu-MOF-based hydrogel composite material.

[0090] Example 4

[0091] This embodiment provides an adenine Cu-MOF-based hydrogel composite material, and the adenine Cu-MOF-based hydrogel composite material is specifically prepared by the following steps:

[0092] (1) First, freeze-dried GelMa was dissolved in deionized water containing LAP at 45°C in the dark to obtain a GelMa solution; then, Cu-AD-SA obtained in Preparation Example 1 was dispersed in the GelMa solution to obtain a mixed solution; finally, the mixed solution was stirred at 45°C in the dark for 15 min to obtain a uniform precursor of a hydrogel composite material;

[0093] The mixed solution includes, by mass percentage, 0.4% Cu-AD-SA, 12% GelMa, 0.1% LAP, and the remainder is water.

[0094] (2) The precursor of the hydrogel composite material obtained in step (1) is irradiated with blue light of 405 nm wavelength, and the cross-linking time is 15 s to obtain the adenine Cu-MOF-based hydrogel composite material.

[0095] Example 5

[0096] This embodiment provides an adenine Cu-MOF-based hydrogel composite material, and the adenine Cu-MOF-based hydrogel composite material is specifically prepared by the following steps:

[0097] (1) First, freeze-dried GelMa was dissolved in deionized water containing LAP at 45°C in the dark to obtain a GelMa solution; then, Cu-AD-SA obtained in Preparation Example 1 was dispersed in the GelMa solution to obtain a mixed solution; finally, the mixed solution was stirred at 45°C in the dark for 15 min to obtain a uniform precursor of a hydrogel composite material;

[0098] The mixed solution includes, by mass percentage, 0.6% Cu-AD-SA, 8% GelMa, 0.3% LAP, and the remainder is water.

[0099] (2) The precursor of the hydrogel composite material obtained in step (1) is irradiated with blue light of 405 nm wavelength, and the cross-linking time is 15 s to obtain the adenine Cu-MOF-based hydrogel composite material.

[0100] Comparative Example 1

[0101] This comparative example provides a hydrogel composite material, which is prepared by the following steps:

[0102] (1) First, freeze-dried GelMa was dissolved in deionized water containing LAP at 45°C in the dark to obtain a GelMa solution; then, HKUST-1 was dispersed in the GelMa solution to obtain a mixed solution; finally, the mixed solution was stirred at 45°C in the dark for 15 min to obtain a uniform precursor of a hydrogel composite material;

[0103] The mixed solution includes, by mass percentage, 0.06% HKUST-1, 10% GelMa, 0.2% LAP, and the remainder is water.

[0104] (2) Irradiating the precursor of the hydrogel composite material obtained in step (1) with blue light of 405 nm wavelength, with a cross-linking time of 15 s, to obtain the hydrogel composite material.

[0105] Comparative Example 2

[0106] This comparative example provides an adenine Cu-MOF-based hydrogel composite material, and the adenine Cu-MOF-based hydrogel composite material is specifically prepared by the following steps:

[0107] (1) First, freeze-dried HAMA is dissolved in deionized water containing LAP at 45° C. in the dark to obtain a HAMA solution; then, Cu-AD-SA obtained in Preparation Example 1 is dispersed in the HAMA solution to obtain a mixed solution; finally, the mixed solution is stirred at 45° C. in the dark for 15 min to obtain a uniform precursor of a hydrogel composite material;

[0108] The mixed solution includes, by mass percentage, 0.06% Cu-AD-SA, 10% HAMA, 0.2% LAP, and the balance is water.

[0109] (2) Irradiating the precursor of the hydrogel composite material obtained in step (1) with blue light of 405 nm wavelength, with a cross-linking time of 15 s, to obtain the hydrogel composite material.

[0110] Comparative Example 3

[0111] This comparative example provides a Cu-MOF-based hydrogel composite material, which is prepared by the following steps:

[0112] S1. Dissolve 0.34 g AgNO3 and 0.374 g Cu(NO3)2·3H2O in 12 mL deionized water, disperse 0.14 g H2PYDC in 12 mL deionized water by ultrasonication, mix the two solutions together and seal them in a steel autoclave, heat them at 120 °C for 24 h, and then centrifuge them at 5000 rpm for 10 min. After precipitation, pour off the supernatant, wash the precipitate three times and dry it at 50 °C for 4 h to obtain bMOF. In bMOF, the Ag ion content is 2 mmol and the Cu ion content is 2 mmol.

[0113] S2. PVA was dissolved in distilled water and stirred continuously at 100 °C for 2 h to form a PVA solution. bMOF was added to the PVA solution under nitrogen protection to make the bMOF content in the final hydrogel 1.2 mg / g.

[0114] S3. Dissolve 0.2 g of chitosan in 10 mL of water and add it to step S2, then drop 5 mL of acetic acid solution to form a viscous sample solution, stir the viscous solution at 45 °C for 45 min, cast it on a plastic mold, and perform vacuum treatment. Then, freeze it at -20 °C for 10 h and thaw it at 20 °C for 5 h. Repeat 4 cycles to obtain a PCbM hydrogel composite material.

[0115] Test Example 1

[0116] MOF cell viability test

[0117] Test samples: copper metal organic framework Cu-AD-SA and HKUST-1 provided in Preparation Example 1;

[0118] Test method: Human immortalized epidermal cells (Hacat) and mouse epithelial fibroblasts (L929) were obtained from the Air Force Specialty Medical Center Cell Bank and cultured in DMEM medium containing 5% fetal bovine serum (FBS) at 37°C and a CO2 concentration of 5%. The two cells were cultured at 1.0×10 4 After the number of cells per well was inoculated in a 96-well plate, the cells were cultured in an incubator. After 24 hours, Cu-AD-SA and HKUST-1 were added to the culture medium to prepare a 400 μg / mL suspension, which was diluted to ten concentrations and added to the 96-well plate for continued culture. After 36 hours of culture, the culture medium containing CCK-8 was added and cultured for another hour, and then the absorbance at 450 nm was detected under an ELISA reader to characterize the activity of the cells.

[0119] Test results:

[0120] like Figure 1As shown, in different concentrations of Cu-AD-SA at 36 h, (a) Hacat cells and (b) L929 fibroblasts, when the concentration of Cu-AD-SA was 50 μg / mL, Cu-AD-SA significantly promoted the proliferation of keratinocytes and also promoted the proliferation of fibroblasts. Comparison of cell viability results of HKUST-1 (c) Hacat cells and (d) L929 fibroblasts at different concentrations showed that Cu-AD-SA had good biocompatibility.

[0121] Therefore, from the perspective of biocompatibility and cell proliferation, the cell viability test results of Cu-AD-SA show that when its concentration is 100 μg / mL, the survival rate of Hacat cells can still reach 124% within 36 hours, and the survival rate of L929 cells can reach 94%. Compared with the classic HKUST-1, at 100 μg / mL, the survival rates of Hacat cells and L929 cells were 63% and 62% within 36 hours, respectively. This shows that Cu-AD-SA has higher biocompatibility than HKUST-1 and has a better effect in promoting keratinocyte proliferation.

[0122] Test Example 2

[0123] X-ray powder diffraction

[0124] Test samples: the copper metal organic framework Cu-AD-SA provided in Preparation Example 1 and the adenine Cu-MOF-based hydrogel composite material prepared in Example 1.

[0125] Test method: 20 mg sample powder was selected and its phase structure was characterized by X-ray powder diffraction at a scanning speed of 10°min -1 , scanning range 5~40°.

[0126] Test results:

[0127] like Figure 2 As shown, the X-ray powder diffraction patterns under different conditions show that the Cu-AD-SA@GelMa composite materials prepared by immersion in room temperature water for 2 days, immersion in 37°C PBS buffer for 2 days, and synthesis are consistent with the simulation peaks, and the material is relatively stable.

[0128] Test Example 3

[0129] Stability test

[0130] Test samples: the copper metal organic framework Cu-AD-SA and HKUST-1 provided in Preparation Example 1.

[0131] Test method: 5 mg of the prepared Cu-AD-SA and HKUST-1 samples were immersed in 10 mL of (1) deionized water at room temperature for 72 h; (2) PBS buffer in a 37°C oven for 72 h, then filtered, the liquid was collected and subjected to ICP testing. The glass bottle was shaken continuously during the immersion process to ensure sufficient reaction.

[0132] The test results are shown in Table 1 below:

[0133] Table 1

[0134]

[0135] As shown in Table 1 above, the copper ion release concentration diagram of Cu-AD-SA and HKUST-1 under different conditions for 72 h shows that the stability of Cu-AD-SA is higher than that of HKUST-1. From the perspective of material stability, after 5 mg Cu-AD-SA was immersed in 10 mL room temperature aqueous solution and 37 °C PBS solution for 72 h, the X-ray powder diffraction peak of the sample was consistent with the theoretical simulation peak of the material, and the concentration of released copper ions was detected to be 1.86 and 0.28 mg / L, respectively, which was lower than the concentration of copper ions released by HKUST-1 under the same conditions, 2.27 and 0.34 mg / L, indicating that Cu-AD-SA has good stability.

[0136] Test Example 4

[0137] Cell cloning experiments

[0138] Test sample: the copper metal organic framework Cu-AD-SA provided in Preparation Example 1.

[0139] Test method:

[0140] (1) Take cells from each group in the logarithmic growth phase, digest them with 0.25% trypsin and blow them into single cells, and suspend the cells in DMEM culture medium containing 10% fetal bovine serum for later use.

[0141] (2) The cell suspension was inoculated into a dish containing 2 mL of 37°C pre-warmed culture medium at a density of 50 cells per dish, and gently rotated to disperse the cells evenly. After culturing in a cell culture incubator at 37°C, 5% CO2 and saturated humidity for 24 h, MOF suspensions with concentrations of 0, 6, 50 and 100 μg / mL were added, respectively.

[0142] (3) Observe after 36 hours. When visible clones appear in the culture dish, terminate the culture. Discard the supernatant and carefully wash twice with PBS. Add 4% paraformaldehyde to fix the cells for 15 minutes. Then remove the fixative and add an appropriate amount of crystal violet to stain for 10-30 minutes. Then slowly wash away the staining solution with deionized water, air dry, and take pictures.

[0143] Test results:

[0144] like Figure 3 As shown, from the perspective of cell proliferation, the cell cloning experiment results of the Cu-MOF showed that the proliferation effect was obvious when its concentration was 50 μg / mL.

[0145] Test column 5

[0146] Cell viability test in 3D co-culture of MOF and hydrogel

[0147] Test samples: the adenine Cu-MOF-based hydrogel composite material prepared in Example 1 and the hydrogel composite materials prepared in Comparative Examples 1 to 3.

[0148] Test method: Human immortalized epidermal cells (Hacat) were obtained from the Air Force Specialty Medical Center Cell Bank and cultured in DMEM medium containing 5% fetal bovine serum (FBS) at 37°C and a CO2 concentration of 5%. 4 The number of cells per well was mixed with 0.06%, 0.5% and 1% MOF@GelMA prepared in Example 1, HKUST-1@GelMa prepared in Comparative Example 1, Cu-AD-SA@HAMA prepared in Comparative Example 2 and 100 μL DMEM solution of bMOF and PCbM hydrogel composite material prepared in Comparative Example 3, inoculated in a 96-well plate, and after cross-linking, 100 μL DMEM solution was added to the upper layer. After 36 h of culture in an incubator, a culture solution containing CCK-8 was added and cultured for 1 h, and then the absorbance of the supernatant at 450 nm was detected under an ELISA instrument to characterize the activity of the cells.

[0149] Test results:

[0150] like Figure 4A As shown in the figure, at 36 h, the hydrogel composites with different contents of Cu-AD-SA, when the content was 6%, Cu-AD-SA@GelMA significantly promoted the proliferation of keratinocytes, indicating that Cu-AD-SA@GelMA has better biocompatibility in more realistic 3D culture. Figure 4BThe composite HKUST-1@GelMa prepared from different Cu-MOFs and GelMA prepared in Comparative Example 1 did not show any effect on promoting keratinocyte proliferation, because HKUST-1 itself is not as good as Cu-AD-SA in promoting keratinocyte proliferation. The Cu-AD-SA@HAMA prepared in Comparative Example 2 may not have a significant ability to promote keratinocyte proliferation due to its air permeability. The MOF and hydrogel composite prepared in Comparative Example 3 showed no significant proliferation phenomenon.

[0151] Test column 6

[0152] Live-dead staining test of cells in 3D co-culture of MOF and hydrogel

[0153] Test sample: adenine Cu-MOF-based hydrogel composite material prepared in Example 1.

[0154] Test method: Place 5% Cu-AD-SA@GelMA containing HaCaT cells in 3D co-culture for 36 h in test column 5 in a small dish for laser confocal microscopy test, remove the upper culture medium liquid, and then wash the gel with PBS (phosphate buffered saline). Add the live cell dye Calcein AM and the dead cell dye PI (propidium iodide) to the gel according to the proportion in the instruction manual. Incubate the cell suspension at 37°C and 5% CO2 for 30 min. After incubation, wash the cells with PBS to remove unbound dye. Use laser confocal microscopy for analysis, and live and dead cells will be distinguished based on their fluorescence characteristics.

[0155] Test results:

[0156] like Figure 5 As shown, the biocompatibility of 3D cultured keratinocytes in the Cu-AD-SA hydrogel composite was good at 36 h.

[0157] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An adenine Cu-MOF-based hydrogel composite material, characterized in that: The adenine Cu-MOF-based hydrogel composite material is composed of a copper metal organic framework loaded on a hydrogel; Wherein, the copper metal organic framework is [Cu2(Ad)2(SA)]·3DMA; Wherein, the hydrogel is methacrylated gelatin; Wherein, the mass ratio of the copper metal organic framework to the hydrogel is (0.1-1):(5-15).

2. The adenine Cu-MOF-based hydrogel composite material according to claim 1, characterized in that: The raw materials for preparing the Cu-MOF-based hydrogel composite material include the following components by mass percentage: The copper metal organic framework is 0.1-1%, the hydrogel is 5-15%, the photocrosslinking agent is 0.05-0.5%, and the balance is the reaction solvent.

3. The adenine Cu-MOF-based hydrogel composite material according to claim 2, characterized in that: The photocrosslinking agent is lithium phenyl (2,4,6-trimethylbenzoyl) phosphinate.

4. The adenine Cu-MOF-based hydrogel composite material according to claim 2, characterized in that: The reaction solvent is water.

5. A method for preparing an adenine Cu-MOF-based hydrogel composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The copper metal organic framework and the hydrogel are sequentially subjected to solvent thermal reaction and photo-crosslinking reaction, so that the copper metal organic framework is loaded on the hydrogel to obtain the adenine Cu-MOF-based hydrogel composite material.

6. The method for preparing the adenine Cu-MOF-based hydrogel composite material according to claim 5, characterized in that: The preparation method specifically comprises the following steps: The copper metal organic framework, the hydrogel, the photocrosslinking agent and the reaction solvent are mixed to perform a solvothermal reaction to obtain a precursor of the hydrogel composite material; The precursor of the hydrogel composite material is subjected to a photo-crosslinking reaction under the condition of blue light to obtain the adenine Cu-MOF-based hydrogel composite material.

7. The method for preparing the adenine Cu-MOF-based hydrogel composite material according to claim 6, characterized in that: The temperature of the solvent thermal reaction is 45-55°C.

8. The method for preparing the adenine Cu-MOF-based hydrogel composite material according to claim 6, characterized in that: The solvent thermal reaction time is 10 to 20 minutes.

9. The method for preparing the adenine Cu-MOF-based hydrogel composite material according to claim 6, characterized in that: The wavelength of the blue light is 400-450nm.

10. The method for preparing the adenine Cu-MOF-based hydrogel composite material according to claim 6, characterized in that: The temperature of the cross-linking reaction is 40-55°C.

11. The method for preparing the adenine Cu-MOF-based hydrogel composite material according to claim 6, characterized in that: The cross-linking reaction time is 10 to 20 seconds.

12. Use of the adenine Cu-MOF-based hydrogel composite material according to any one of claims 1 to 4 in preparing a material for promoting skin wound healing and / or preparing a material for promoting keratinocyte proliferation.

Citation Information

Patent Citations

  • Administration of cells and cellular extracts for rejuvenation

    AU2012201710A1

  • Triazolyl biological MOF (Metal Organic Framework) material as well as preparation method and application thereof

    CN112979971A